Vogt Koyanagi Harada Disease In Paediatric Age Group: Clinical Characteristics, Remission, Recurrences and Complications in Asian Indian Population. (17th February 2022) - Kaza, Hrishikesh; Tyagi, Mudit; Agarwal, Komal; Behera, Shashwat; Pappuru, Rajeev R; Mohan, Sashwanthi; Saldanha, Merlin; Videkar, Chetan; Basu, Soumyava; Pathengay, Avinash; Murthy, Somasheila
ABSTRACT: Purpose: To describe disease characteristics and outcomes of Vogt-Koyanagi-Harada (VKH) syndrome in paediatric patients. Study Design: Retrospective chart analysis Methods: A retrospective: Analysis of all patients ≤16 years with VKH syndrome was done. Clinical presentations, complications, recurrences and outcomes in cases of paediatric VKH were reviewed. Results: 72 eyes of 36 patients with a mean age at presentation of 13.7 ± 2.34 years were assessed. Mean duration of symptoms and follow up were 9.88 ± 17.3 weeks and 55 months respectively. Clinical signs at presentation included anterior chamber cells >2+(34/72eyes, 47.2%), granulomatous keratic precipitates (6 eyes, 8.3%), posterior synechiae (35 eyes, 48.6%), disc edema (46 eyes, 63.8%), neurosensory retinal detachments (44 eyes, 61.1%) and 'sunset-glow' fundus (9 eyes, 12.5%). Best corrected visual acuity (BCVA) at the time of presentation was 1.3logMAR or a Snellens equivalent of 20/400 which improved to 0.51logMAR (Snellens equivalent of 20/63) at last follow up. Remission was achieved in 61.1% cases. More than half of our patients developed one or more complications. Conclusion: VKH in paediatric patients poses a challenge due to a delayed presentation and paediatric VKH patients have a worse visual acuity at the time of presentation as compared to adult age groups. Rates of remission may be low along with high risk of complications and hence there is a need for prolonged immunosuppression.